Relationship Between Subclinical Renal Damage and Maximum Rate of Blood Pressure Variation Assessed by Fourier Analysis of 24-h Blood Pressure Curve in Patients with Essential Hypertension - Caterina Carollo; Alessandra Sorce; Maria Giovanna Vario; Emanuele Cirafici; Davide Bologna; Maria Elena Ciuppa; Salvatore Evola; Guseppe Mulè; Giulio Geraci (Life)
Background: Blood pressure (BP) variability has been increasingly recognized as a predictor of cardiovascular and renal outcomes. However, the relevance of specific dynamic indices such as the maximum slope of systolic blood pressure (max SBP slope), derived through partial Fourier series modeling, in relation to early renal damage remains underexplored. Methods: A total of 389 patients with essential hypertension were enrolled and stratified according to the estimated glomerular filtration rate (eGFR) ≥ or <90 mL/min/1.73 m2 and the presence of subclinical renal damage, defined by elevated urinary albumin excretion (AER) and/or reduced eGFR. All participants underwent clinical and biochemical evaluation, as well as 24-h ambulatory blood pressure monitoring (ABPM), including advanced hemodynamic analysis using Fourier-based modeling. Results: Patients with eGFR < 90 mL/min/1.73 m2 were older and exhibited higher waist circumference, uricemia, albuminuria, and systolic BP values, including the elevated max SBP slope (12.8 vs. 10.8 mmHg/h, p = 0.028). Subclinical renal damage was associated with older age; male sex; smoking; and higher levels of uricemia, clinical, and ambulatory BP, and the max SBP slope (14.2 vs. 10.7 mmHg/h, p = 0.007). The max SBP slope positively correlated with AER (r = 0.215, p < 0.001) and inversely with eGFR (r = −0.153, p = 0.002). In multivariate linear regression, the max SBP slope remained independently associated with AER (β = 0.220, p < 0.001), along with mean 24-h SBP, male sex, and the day–night SBP percentage dip. Logistic regression confirmed these associations with subclinical renal damage (max SBP slope OR: 1.536; 95% CI: 1.241–2.004; p = 0.001). Conclusions: The max SBP slope, a dynamic index of BP derived via Fourier analysis, is independently associated with markers of subclinical renal damage in hypertensive patients. This suggests that incorporating such advanced metrics into ABPM evaluation may improve early risk stratification and help identify individuals at greater risk of renal impairment, even in the absence of overt kidney disease.